2015
DOI: 10.1186/s13063-015-0645-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Ban-Lan-Gen granules in the treatment of seasonal influenza: study protocol for a randomized controlled trial

Abstract: BackgroundBan-Lan-Gen (BLG) is a traditional Chinese herbal medicine. It has been used for the prevention and treatment of virus-related respiratory diseases such as influenza virus infection. BLG contains some antiviral compounds, but few evidence-based clinical studies have been conducted to assess its efficacy against influenza. We assessed the effects of BLG (including efficacy and safety) on the treatment of seasonal influenza in an evidence-based clinical trial.Methods/DesignWe conducted a randomized, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Based on the current evidence23 of oseltamivir in treating seasonal influenza24 and the patient’s disease burden, we also referenced the course of treatment of another Chinese prescription Lianhuaqingwen capsule25 in treating influenza. Participants in each group will receive treatment for 5 days and observation for 21 days, and will be followed up by research interviewers on days 1, 3, 5, 7 and 21 after treatment26; the study flowchart is shown in figure 1.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Based on the current evidence23 of oseltamivir in treating seasonal influenza24 and the patient’s disease burden, we also referenced the course of treatment of another Chinese prescription Lianhuaqingwen capsule25 in treating influenza. Participants in each group will receive treatment for 5 days and observation for 21 days, and will be followed up by research interviewers on days 1, 3, 5, 7 and 21 after treatment26; the study flowchart is shown in figure 1.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Radix isatidis (Ban lan gen) is a popular herbal medicine, especially after the severe acute respiratory syndrome (SARS) epidemic, for its clinical applications in upper respiratory tract infections, including the nose, throat, and sinuses [210]. It is also prescribed for other viral infections like measles and hepatitis [211,212], etc.…”
Section: Role Of Manipulating Autophagy In the Pathogenesis Of Hummentioning
confidence: 99%
“…• English translation: "Find out Banlangen (a traditional Chinese herbal medicine. It has been used for the prevention and treatment of virus-related respiratory diseases such as influenza virus infection [32]. whether it is useful or not.…”
mentioning
confidence: 99%